2016
DOI: 10.4085/1062-6050-51.10.14
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With and Perceptions of Workplace Bullying Among Athletic Trainers in the Secondary School Setting

Abstract: Context: Workplace bullying (WPB) has recently received much attention in society. Research on WPB in athletic training practice settings is limited.Objective: To determine the prevalence of WPB in the secondary school setting and explore the factors related to it.Design: Mixed-methods study. , aged 36.5 6 11.1 years with 11.9 6 9.5 years of experience took part in phase I. Ten participants (7 women and 3 men), aged 39.3 6 10.1 years with 14.3 6 8.3 years of experience, took part in phase II.Data Collection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Lateral hostilities among emergency and critical care nurses have been associated with SPs in victims (Bambi et al, 2013), and the same phenomenon has been observed in Turkish hospital nurses (Ovayolu et al, 2014). Lateral violence was among the predictors of insomnia in a longitudinal study on Norwegian shift nurses (Vedaa et al, 2016) and in many studies that focused specifically on workplace bullying (Lallukka et al, 2011; Rodriguez-Munoz and Notelaers, 2011; Ziemska et al, 2013; Hansen et al, 2014, 2016; Kostev et al, 2014; Magee et al, 2015; Bonde et al, 2016; Pitney et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Lateral hostilities among emergency and critical care nurses have been associated with SPs in victims (Bambi et al, 2013), and the same phenomenon has been observed in Turkish hospital nurses (Ovayolu et al, 2014). Lateral violence was among the predictors of insomnia in a longitudinal study on Norwegian shift nurses (Vedaa et al, 2016) and in many studies that focused specifically on workplace bullying (Lallukka et al, 2011; Rodriguez-Munoz and Notelaers, 2011; Ziemska et al, 2013; Hansen et al, 2014, 2016; Kostev et al, 2014; Magee et al, 2015; Bonde et al, 2016; Pitney et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Specific bullying characteristics are analysed in basketball (Vveinhardt et al), football (Yildiz & Alpkan, 2015), athletics (Myers, 2016), ice hockey (Kurudirek, 2015), and others. There are various possible sources of bullying, for example, sports persons (Kurudirek, 2015), coaches (Pitney et al, 2016), assistants such as a doctor of a team (Marks et al, 2012), spectators or fans of sports events (Courtney, Wann, 2010). Respondents of such surveys confess that they are humiliated, summoned, isolated, they do not receive the necessary attention or support and burn down in their sport.…”
Section: Research Area Of Bullying and Harassment As Antisocial Behaviours In Sportmentioning
confidence: 99%
“…We found that the research on bullying and harassment in sport is not that frequent. The located studies only detected ongoing bullying among sports coaches (Pitney et al, 2016) or judges (Hacicaferoglu, 2015), but there were no studies that revealed the effects of this phenomenon on the athlete. However, the idea that the interaction of an athlete and a coach or an athlete and an athlete's manager is particularly important in sport and the negative effects of bullying in the sports sector can have a significant impact on both sports persons and their ability to manage bullying, which has impact on sports organization management.…”
Section: Research Area Of Bullying and Harassment As Antisocial Behaviours In Sportmentioning
confidence: 99%
See 2 more Smart Citations